Light weight non-metallic lightning strike protection film for CFRP. (December 2020) - Zhao, Zhongjie; Ma, Yingjian; Yang, Zheng; Yu, Jinguang; Wang, Jin; Tong, Jianfeng; Yi, Xiaosu; Moreira, Pedro; Sguazzo, Carmen
Abstract: To reduce the weight of state-of-the-art aeronautical lightning protection material, a non-metallic lightning strike protection film was prepared. The new film consisted of 2 functional layers, which were capable of dispersing lightning current and blocking heat propagation from lightning plasma, respectively. Graphene and conductive polymer veil were adopted as electrical conductivity modifier; expandable graphite was adopted as thermal insulator. By integrating these functions, the new film featured by light weight, good bonding strength and lightning protection effectiveness, the lightning damage depth reduced by 79 % and the residual compression strength was increased by 21 %. This paper proposed and verified that establishing synergistic system which respond to electrical and thermal induced lightning damage simultaneously could remarkably increase the lightning protection effectiveness of CFRP, the prospect of this new technique was also discussed.